1. Panorama społeczna Kirgistanu .......... 169 - Panasiuk, Paweł (Kirgistan – oblicza transformacji, 2020)
THE SOCIAL PANORAMA OF KYRGYZSTANThe purpose of this chapter is to show the demographic changes in Kyrgyz society that took place in 2014-2018, mainly based on statistical data. The issues of family and tribal relationships and the importance of religion are also tackled. The analysis of demographic indicators shows that in modern Kyrgyzstan there is still an increase in the total number of population, as well as the share of people of pre-working age in the age structure of society, which also affects the economic development of the country.